2020
DOI: 10.1007/s00468-020-02046-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental condition on the creation of organic compounds in Pinus sylvestris L. rhizosphere, roots and needles

Abstract: Key message Studied organic molecules in Pinus sylvestris L. seem to have acted as a safety net for metal transport, chelation and sequestration, allowing adaptation and growth under highly polluted conditions. Abstract Pinus sylvestris L. is known for its ability to survive in areas of highly elevated metal pollution, such as flotation tailings. The aim of the study was to estimate the content of selected organic molecules (including aliphatic low molecular weight organic acids (ALMWOAs), phenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Concentrations of organic acids have been observed to increase in needles with increasing temperature [6] and in polluted soil environments [17], suggesting their role in needle maintenance and repair from heat stress. However, our understanding of the variability in secondary metabolites in Scots pine needles in natural forest ecosystems is not well documented, nor do we have a clear understanding of the influence of tree age or season on this variation.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of organic acids have been observed to increase in needles with increasing temperature [6] and in polluted soil environments [17], suggesting their role in needle maintenance and repair from heat stress. However, our understanding of the variability in secondary metabolites in Scots pine needles in natural forest ecosystems is not well documented, nor do we have a clear understanding of the influence of tree age or season on this variation.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of organic acids have been observed to increase in needles with increasing temperature (Churakova et al 2019) and in polluted soil environments (Magdziak et al 2021), suggesting their role in needle maintenance and repair from heat stress.. However, our understanding of the variability in secondary metabolites in Scots pine needles in natural forest ecosystems is not well documented, nor do we have a clear understanding of the in uence of tree age or season on this variation.…”
Section: Introductionmentioning
confidence: 99%
“…The most important of them are α-Pinene, δ-3-carene, germacrene-4-ol, and bornyl acetate. The main sesquiterpenes are β-caryophyllene, germacrene D, bicyclogermacrene, δ-cadinene, γ-cadinene, germacrene D-4-ol, cubenol and α-cadinol [4,5]. Research has shown that essential oil exhibits antiparasitic, anti-hyperglycemic, anti-allergenic, anti-viral, anti-spasmodic properties, as well as insecticidal and larvicidal properties [6,7].…”
Section: Introductionmentioning
confidence: 99%